PENERAPAN METODE PEMBELAJARAN KUANTUM UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMPN 6 MUARO BUNGO - Purba, Dea Laura; Rasdawita; Hilman Yusra; Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the low descriptive writing skills of seventh-grade students at SMPN 6 Muaro Bungo. The aim of this study was to improve students' descriptive writing skills through the application of the Quantum Learning method. This study was a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four main stages: planning, implementation, observation, and reflection. The subjects were 20 seventh-grade students at SMPN 6 Muaro Bungo. Data were collected using test techniques (written descriptive writing tests) and non-test techniques (observation sheets for teacher and student activities). Data were analyzed quantitatively to assess learning outcomes. The results showed that the Quantum Learning method was effective in gradually improving students' writing skills. This was evidenced by a significant increase in the percentage of students' classical completion, from only 5% in Cycle I to 55% in Cycle II. In addition to boosting learning outcomes, the implementation of this method was also proven to increase students' motivation and active participation during the learning process.